Gender differences in the association of insomnia symptoms and coronary artery calcification in the multi-ethnic study of atherosclerosis. Issue 10 (14th May 2021) - Bertisch, Suzanne M; Reid, Michelle; Lutsey, Pamela L; Kaufman, Joel D; McClelland, Robyn; Patel, Sanjay R; Redline, Susan
Abstract: Study Objectives: To quantify the gender-specific associations between insomnia symptoms and subclinical atherosclerosis, measured by coronary artery calcium (CAC) scores, which has strong predictive value for incident cardiovascular disease. Methods: We analyzed data from 1, 429 participants in the Multi-Ethnic Study of Atherosclerosis (MESA). Participants completed standardized questionnaires and underwent polysomnography (PSG) and 7-day actigraphy. Insomnia symptoms were defined as: self-reported trouble falling, staying or returning to sleep, early-morning awakenings, or hypnotic use, for ≥5 nights/week. MESA assessed CAC using computed tomography. We employed multivariable linear regression to model the probability of CAC >0 overall and to model the linear continuous effect among those with nonzero CAC. Results: Our sample was a mean age of 68.1 ± 9.1 years, 53.9% female, and 36.2% white, 28.0% black, 24.2% Hispanic, and 11.5% Chinese-American. Insomnia symptoms were present in 49.7% of men and 47.2% of women. In multivariable-adjusted analyses, insomnia symptoms was associated with an 18% higher prevalence of CAC (PR 1.18, 95% CI 1.04, 1.33) among females, but no association was observed among males (PR 1.00, 95% CI 0.91, 1.08). There was no evidence that the association between insomnia symptoms and prevalence of CAC >0 differed by objective sleep duration status (by single-night PSG or multi-night actigraphy) in females or males. Conclusions: We found that among women, insomnia symptoms were associated with an 18% higher prevalence of CAC compared to no insomnia. Insomnia symptoms were not associated with CAC prevalence in men. Additionally, there was no evidence that the association between insomnia symptoms and CAC score >0 differed by objective short sleep duration status.